THE EFFECT OF FOREIGN INVESTMENT, NET EXPORTS, AND TOURIST ARRIVALS ON ECONOMIC GROWTH IN ASEAN COUNTRIES: AN ISLAMIC ECONOMIC PERSPECTIVE (2019–2023) - Dela Sisilia; Muhammad Iqbal; Ghina Ulfah Saefurrohman (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
Asean was formed with the aim of accelerating the economic growth of its member countries. However, the facts show that the economic growth of Asean countries is still fluctuative and unstable. This study aims to determine the influence of Foreign Investment, Net Exports, and the Number of Tourist Visits on Economic Growth in Asean Countries in the Perspective of Islamic Economics. This study uses panel data from ten ASEAN countries. The results of the study show that the selected model is the Fixed Effect Model test which states that the variable foreign investment has an effect on economic growth, net exports have no effect on economic growth, and the number of tourist visits has an effect on economic growth. The F-test indicates that the variables jointly affect economic growth in Asean countries